O4C.2 Impact of precarious work on the wellbeing of women and migrants in australia. (April 2019) - Reid, Alison; Daly, Alison; Schenker, Marc
Abstract : Introduction: Women and migrants are more likely to be in precarious work than men and native-born workers. Precarious work impacts adversely on work-related injuries, fatalities and health but little is known about how it affects the wellbeing of women and migrant workers. The aims of this study are; (1) to examine whether precarious work differs by migration status and sex and 2) to determine whether the impact of precarious work on the wellbeing of women and migrants differs to that of males and native-born workers. Methods: In 2016/17 a national telephone survey examined psychosocial workplace hazards among 1630 migrant and 1051 Australian-born workers. Precarious work (vulnerability and job insecurity) and wellbeing were collected with sociodemographic and employment variables. Higher scores indicate greater vulnerability/insecurity/less wellbeing. Univariate statistics examined the association between precarious work and wellbeing by sex and country of birth. Stratified linear regression modelled the relationship between precarious work and wellbeing by sex. Results: Independent of country of birth, females had higher vulnerability (µ=6.5, σ=3.4) than males (µ=5.5, σ=3.6), in contrast to job insecurity (Women µ=8.2, σ=4.0; Men µ=8.2, σ=3.9). Workers born in the Philippines had higher vulnerability compared with other migrant workers (µ=6.6, σ=3.4 vs µ=5.9, σ=3.6) whereas workers born in India had higher employment insecurity compared with other migrant workers (µ=8.8, σ=4.1 vs µ=8.1, σ=3.9). Increasing vulnerability and insecurity adversely impacted wellbeing most in Australian workers. Compared with men, vulnerability had a greater adverse impact on the wellbeing of women. Discussion: Two dimensions of precarious work impact the wellbeing of men and women differently. Vulnerability impacts women most whereas work insecurity impacts men. For Australian born, the impact of either dimension on wellbeing is greater than for migrant workers.